Optimised reinforcement patterns for short span bridges - Teo, Wee (2000)
Reinforced concrete beams with adjusted reinforcement, i.e. beams with an ‘optimised’ reinforcement layout which follows the principle stress trajectories of an elastic beam, have been found to give substantial increases in load capacity compared with simple beams without stirrups. At Queen’s University Belfast, tests on beams with a simple adjusted reinforcement were conducted in order to assess the effect of load position on the load capacity of such beams and to develop theoretical analysis methods for complex reinforcement patterns further. The tests showed that even simple adjustment improves the load capacity by 32% and determined the most critical load position for the development of the reinforcement layout. Truss modeling of such complex situations proved an accurate method to predict the reinforcement areas required in the beams.